2020
DOI: 10.1038/s41467-020-15686-y
|View full text |Cite
|
Sign up to set email alerts
|

Brain insulin sensitivity is linked to adiposity and body fat distribution

Abstract: Brain insulin action regulates eating behavior and energy fluxes throughout the body. However, numerous people are brain insulin resistant. How brain insulin responsiveness affects long-term weight and body fat composition in humans is still unknown. Here we show that high brain insulin sensitivity before lifestyle intervention associates with a more pronounced reduction in total and visceral fat during the program. High brain insulin sensitivity is also associated with less regain of fat mass during a nine ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
92
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(104 citation statements)
references
References 36 publications
8
92
0
4
Order By: Relevance
“…In either case, there remains limited data in humans with obesity or T2D confirming the effects of exercise on brain insulin sensitivity in relation to glucose metabolism. It was shown that lifestyle modification inducing weight loss, including increased physical activity and low-fat diet, increased brain insulin sensitivity in people with obesity as assessed by intranasal insulin spray ( 107 ). Moreover, Honkala et al ( 108 ) demonstrated in sedentary middle-aged adults with insulin resistance sprint interval training for 2 weeks lowered insulin-stimulated glucose uptake in the temporal cortex, cingulate gyrus, cerebellum as well as global regions when compared with moderate continuous training.…”
Section: Metformin and Exercise On Brain Insulin Sensitivitymentioning
confidence: 99%
“…In either case, there remains limited data in humans with obesity or T2D confirming the effects of exercise on brain insulin sensitivity in relation to glucose metabolism. It was shown that lifestyle modification inducing weight loss, including increased physical activity and low-fat diet, increased brain insulin sensitivity in people with obesity as assessed by intranasal insulin spray ( 107 ). Moreover, Honkala et al ( 108 ) demonstrated in sedentary middle-aged adults with insulin resistance sprint interval training for 2 weeks lowered insulin-stimulated glucose uptake in the temporal cortex, cingulate gyrus, cerebellum as well as global regions when compared with moderate continuous training.…”
Section: Metformin and Exercise On Brain Insulin Sensitivitymentioning
confidence: 99%
“…Dear Sir, In a recent study by Kullmann and colleagues [1], the authors showed that brain insulin sensitivity predicts weight loss at follow-up of nearly 10 years. Furthermore, in a crosssectional experiment, good hypothalamic insulin responsiveness was associated with lesser visceral fat mass, while no correlation was detected with subcutaneous fat mass.…”
mentioning
confidence: 99%
“…Furthermore, fibroblast growth factor 21 (FGF21), a hepatocyte-derived hormone, signals protein and glucose status to the brain, allowing the refinement of food choice and metabolism according to dietary changes [ 16 , 17 ]. On the other hand, CNS insulin sensitivity modulates adiposity and body fat accumulation [ 18 ]. Along the brain-periphery signaling network, diet and microbiota deeply influence these communication pathways through several mechanisms.…”
Section: Nutrients Microbiota and Brain Healthmentioning
confidence: 99%